f(x)=square root x+2 then outside the square root -3.
Can someone help explain how to graph this and also whats being done to this fuction y=-2f(x+3)-1
Thanks for the help.
so lets start with the basic function $\displaystyle h(x) =\sqrt{x}$
Then $\displaystyle h(x+2)=\sqrt{x+2}$ This shifts the graph two units to the left on the x axis.
finally $\displaystyle f(x)=h(x+2)+3$ the + 3 shifts the graph up 3 units in the y direction.
see the attached graph.
This should help with the second part as well